2017
DOI: 10.1021/acs.est.6b03530
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Eight Different Polymers under Uncontrolled Composting Conditions: Relationships Between Deterioration, Biofilm Formation, and the Material Surface Properties

Abstract: With the ever-increasing volume of polymer wastes and their associated detrimental impacts on the environment, the plastic life cycle has drawn increasing attention. Here, eight commercial polymers selected from biodegradable to environmentally persistent materials, all formulated under a credit card format, were incubated in an outdoor compost to evaluate their fate over time and to profile the microbial communities colonizing their surfaces. After 450 days in compost, the samples were all colonized by multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…General biodegradable plastics have mainly been evaluated for their biodegradability in soil environments. In a previous study, the degradation and biofilm formation of eight different plastics were evaluated under uncontrolled composting conditions ( 18 ). Two out of five polyesters, PBS and PHA, showed low, but significant weight loss after a 450-d incubation in compost.…”
Section: Discussionmentioning
confidence: 99%
“…General biodegradable plastics have mainly been evaluated for their biodegradability in soil environments. In a previous study, the degradation and biofilm formation of eight different plastics were evaluated under uncontrolled composting conditions ( 18 ). Two out of five polyesters, PBS and PHA, showed low, but significant weight loss after a 450-d incubation in compost.…”
Section: Discussionmentioning
confidence: 99%
“…The roughness and hydrophobicity of microplastics constitute the most prominent parameters controlling microplastic surface properties and hence can greatly influence microbial community structure (Gong et al 2019 ; Mercier et al 2017 ). Aged-microplastics, produced via exposure to UV light or incubation in water for several weeks, usually have increased surface area, roughness and polarity compared to virgin samples (Brennecke et al 2016 ; Jemec Kokalj et al 2019 ; Liu et al 2019 ; Liu et al 2020 ).…”
Section: Factors Influencing the Formation Of Microplastic Biofilmsmentioning
confidence: 99%
“…PHBV and PBSA polyesters have very good biodegradability performances in various environments compared to other biodegradable polymers [6][7][8]. Poly(3-hydroxybutyrate) is actually considered as a suitable alternative for cellulose as a reference material in the standards of biodegradation for soil and water environments, respectively NF EN 17033 and ISO DIS 14852.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Yang et al [8] have shown that PBSA and PCL biodegraded better than other polymers (PP, PLLA, PBS) in the same compost but the performance and mechanisms of biodegradation were not further investigated. The study of Mercier [7] compared the degradation of different polymers (EVOH, PP, PBAT, PET, PBS, scl-PHA, PLLA, PA66) in an uncontrolled compost simulating home composting conditions (average temperature of 13°C) and found that PBS and scl-PHA were the polymers which degraded the most with a mass loss of 5.5 and 8%, respectively after 450 days of incubation.…”
Section: Introductionmentioning
confidence: 99%